Clean automotive technology: Hydraulic hybrid vehicles (HHVs) - Bonab, R.S.; Rahman, S. (Applied Mechanics and Materials, 2012)
In order to reducing emission of internal combustion engines and reducing fuel consumption nowadays, human try to discover efficient internal combustion engines and green engines to protect environment. From last years, there were technologies like turbocharger, hybrid electric and different ways of fuel injection into engine and some others that those were effective in that time. By developing technology human need more efficient engine than past. Also, those technologies have some drawbacks so necessity of new technology is sensible. The new technology that developed by EPA (Environmental Protection Agency). HHVs are hybrid vehicle that use pressurized fluid instead of electric power as alternative power source along with internal combustion engine. Hybrid hydraulic vehicles consist of two important part high pressure hydraulic fluid vessels called accumulators, and hydraulic drive pump/motors. These types of vehicles do not need batteries that use in electric vehicle and it is one of expensive part of HEVs.